Vascular and neural stem cells in the gut: do they need each other? - Schrenk, Sandra; Schäfer, Karl Herbert (Histochemistry and cell biology, 2014)
Enteric neurons and blood vessels form intricate networks throughout the gastrointestinal tract. To support the hypothesis of a possible interaction of both networks, we investigated whether primary mesenteric vascular cells (MVCs) and enteric nervous system (ENS)-derived cells (ENSc) depend on each other using two- and three-dimensional in vitro assays. In a confrontation assay, both cell types migrated in a target-oriented manner towards each other. The migration of MVCs was significantly increased when cultured in ENSc-conditioned medium. Co-cultures of ENSc with MVCs resulted in an improved ENSc proliferation and differentiation. Moreover, we analysed the formation of the vascular and nervous system in developing mice guts. It was found that the patterning of newly formed microvessels and neural stem cells, as confirmed by nestin and SOX2 stainings, is highly correlated in all parts of the developing gut. In particular in the distal colon, nestin/SOX2-positive cells were found in the tissues adjacent to the capillaries and in the capillaries themselves. Finally, in order to provide evidences for a mutual interaction between endothelial and neural cells, the vascular patterns of a RET(−/−) knockout mouse model as well as human Hirschsprung’s cases were analysed. In the distal colon of postnatal RET(−/−) knockout mice, the vascular and neural networks were similarly disrupted. In aganglionic zones of Hirschsprung’s patients, the microvascular density was significantly increased compared with the ganglionic zone within the submucosa. Taken together, these findings indicate a strong interaction between the enteric nervous and vascular system.